HUBUNGAN SIKAP DAN PERILAKU SISWA SERTA MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA DI SEKOLAH - Abd. Aziz Hsb. (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2022)
Learning outcomes as a form of output in the learning process, where the output gets quality learning outcomes, and has a positive influence on the quality of a student. Producing maximum learning outcomes cannot be done without good management of the learning process, as a teacher, it takes the ability to create, grow, develop students' attitudes and behavior in learning and student learning motivation, the existence of attitudes and behavior and learning motivation will be able to have an impact positive effect on the quality of the learning process carried out in schools. Therefore, in this study the researchers wanted to examine and analyze the attitudes and behavior as well as student learning motivation on student learning outcomes at school. This study was conducted using a quantitative method, because this study wanted to analyze the relationship between study variables. Research data were analyzed using correlation and regression analysis, data were collected using a questionnaire in the form of instruments related to the three research variables, the instruments were arranged using a Likert scale. From the results of the study it was found that the attitudes and behavior of students in learning have a positive relationship to student learning outcomes at school, student learning outcomes achieved can be influenced by the attitudes and behavior of students, the better the attitudes and behavior of students in learning, it will produce better learning outcomes. more maximal. Likewise with learning motivation, it has a positive relationship to student learning outcomes at school, the existence of good learning outcomes can be produced with high learning motivation. Thus producing high learning outcomes a teacher as an educator needs to pay special attention and handle to the formation of student learning attitudes and behavior and foster student learning motivation so that students are motivated to always try and be enthusiastic in carrying out the learning process which is expected to improve self-quality and produce high learning outcomes as well